The evolution of macrosystems biology. Issue 1 (1st February 2021) - LaRue, Elizabeth A; Rohr, Jason; Knott, Jonathan; Dodds, Walter K; Dahlin, Kyla M; Thorp, James H; Johnson, Jeremy S; Rodríguez González, Mayra I; Hardiman, Brady S; Keller, Michael; Fahey, Robert T; Atkins, Jeff W; et al.
Abstract : In an era of unprecedented human impacts on the planet, macrosystems biology (MSB) was developed to understand ecological patterns and processes within and across spatial and temporal scales. We used machine‐learning and qualitative literature review approaches to evaluate the thematic composition of MSB from articles published since the 2010 creation of the US National Science Foundation's MSB Program. The machine‐learning analyses revealed that MSB articles studied scale and human components similarly to six ecology subdisciplines, indicating that MSB has deep ecological roots. A comparison with 84, 841 ecological studies demonstrated that MSB has extended the knowledge space of ecology by examining large‐scale patterns and processes alongside anthropogenic factors, which was also confirmed by the qualitative literature review approach. Our analyses indicated that MSB emphasizes large scales, has deep roots in ecological disciplines, and may emerge as a new research frontier, but this last point has yet to be proven.